2019
DOI: 10.1002/ijgo.12901
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of weight gain between levonorgestrel and etonogestrel implants after 12 months of insertion

Abstract: Objective To compare weight gain between women using etonogestrel implants and those using levonorgestrel implants 12 months after insertion. Methods A multicenter prospective cohort study was performed on women recruited from family planning clinics between July 2016 and August 2017. The main study outcome was mean weight gain after 12 months of insertion of the implants. Results The present study included 150 women (age range 18–45 years) using levonorgestrel implants and 167 women using etonogestrel implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In a following multicentre trial by Meirik et al [84], the quicker insertion of ENG implant than LNG subdermal dispositive was confirmed (51 vs. 88 s for ENG and LNG groups, respectively); however, at a six-week follow-up after insertion, no significant difference in terms of complication rates at the level of the insertion site was observed [84]. More recently, Okunola et al [85] reported that 12 months after insertion, in the LNG group, weight gain was significantly higher than in the ENG group (3.16 ± 4.08 vs. 0.77 ± 3.76, p = 0.013; RR 1.69, 95%CI 1.46-1.96). The weight gain in the LNG group was in the range of −5.22 to 19.03 and in the etonogestrel group was in the range of −8.29 to 11.63 [85].…”
Section: Implanonmentioning
confidence: 95%
See 2 more Smart Citations
“…In a following multicentre trial by Meirik et al [84], the quicker insertion of ENG implant than LNG subdermal dispositive was confirmed (51 vs. 88 s for ENG and LNG groups, respectively); however, at a six-week follow-up after insertion, no significant difference in terms of complication rates at the level of the insertion site was observed [84]. More recently, Okunola et al [85] reported that 12 months after insertion, in the LNG group, weight gain was significantly higher than in the ENG group (3.16 ± 4.08 vs. 0.77 ± 3.76, p = 0.013; RR 1.69, 95%CI 1.46-1.96). The weight gain in the LNG group was in the range of −5.22 to 19.03 and in the etonogestrel group was in the range of −8.29 to 11.63 [85].…”
Section: Implanonmentioning
confidence: 95%
“…More recently, Okunola et al [85] reported that 12 months after insertion, in the LNG group, weight gain was significantly higher than in the ENG group (3.16 ± 4.08 vs. 0.77 ± 3.76, p = 0.013; RR 1.69, 95%CI 1.46-1.96). The weight gain in the LNG group was in the range of −5.22 to 19.03 and in the etonogestrel group was in the range of −8.29 to 11.63 [85]. The mean weight difference in the levonorgestrel group was 3.16 (p = 0.004), while in the etonogestrel group it was 0.77 (p = 0.041); no difference in menstrual irregularities and client satisfaction was observed between groups [85].…”
Section: Implanonmentioning
confidence: 96%
See 1 more Smart Citation
“…In a non-randomised trial, the second generation two rod LNG implant Jadelle® was found to have induced similar weight increases to the single rod etonogestrel (ENG) implant Implanon®, with weight gains of approximately 3 vs 1 kg for the Copper IUD users over a 3 year period [22] . In another study, two rod LNG implant users showed greater weight gain compared to the ENG implant users [13] . Other studies have found no differences between the ENG implant compared to other methods [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 91%
“…Although many studies report weight gain in users of a range of POCs [ [2] , [3] , [4] , 6 , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ], the literature has focused primarily on depot medroxyprogesterone acetate (DMPA) delivered as an intramuscular injection 150 mg/ml (IM) with studies reporting weight gain of up to 2–3 kg in the first year of use [ [8] , [9] , [10] , 16 , 20 , 21 ], followed by gains of between 4 and 10 kg with longer term use of 3–5 years [ 2 , 15 , [17] , [18] , [19] ].…”
Section: Introductionmentioning
confidence: 99%